"Effects of langauge proficiency and attitude on achievement in Yoruba essay writing of senior secondary students in Ibadan metropolis, Oyo state " (2014)
"This study examines the effects of language proficiency and attitude on students ’ achievement in Yoruba essay writing. A descriptive survey research design of correlational type was adopted for the study. Three research questions were generated. Using 200 students randomly selected from Senior Secondary schools in Ibadan Metropolis. Three instruments were used and data obtained were analyzed using Pearson Product Moment Correlation Analysis and Multiple Regression Analysis. The findings are as follow: The language proficiency positively correlates with achievement in Yoruba essay writing (r = 0.317, p<0.001) and students’ attitude to Yoruba essay writing (r= 0.292, p<0.05). It reveals significant joint contribution of the independent variables (language proficiency and students attitude to achievement in Yoruba essay writing) to the prediction of achievement in Yoruba essay writing. The result yielded a coefficient of multiple regressions R = 0.658 and multiple R-square = 0.433.3. This shows that, the two predictor factors (language proficiency and students attitude to achievement in Yoruba essay writing) are potent predictors of achievement in Yoruba essay writing. The more potent factor was language proficiency (Beta = .473, t-8.214, P<0.001); and followed by students attitude to Yoruba essay writing (Beta = .146, t = 2.594, P<0.05). Based on these results, appropriate recommendation on ways to improve the performance of students in Yoruba essay writing is made in the body of the paper "